An Undergraduate Laboratory Activity Demonstrating Bacteriophage Specificity - Mary E. Allen (American Society for Microbiology, 2013)
Bacteriophage are among the most diverse and numerous microbes inhabiting our planet. Yet many laboratory activities fail to engage students in meaningful exploration of their diversity, unique characteristics, and abundance. In this curriculum activity students use a standard plaque assay to enumerate bacteriophage particles from a natural sample and use the scientific method to address questions about host specificity and diversity. A raw primary sewage sample is enriched for bacteriophage using hosts in the family Enterobacteriaceae. Students hypothesize about host specificity and use quantitative data (serial dilution and plaque assay) to test their hypotheses. Combined class data also help them answer questions about phage diversity. The exercise was field tested with a class of 47 students using pre- and posttests. For all learning outcomes posttest scores were higher than pretest scores at or below p = 0.01. Average individualized learning gain (G) was also calculated for each learning outcome. Students’ use of scientific language in reference to bacteriophage and host interaction significantly improved (p = 0.002; G = 0.50). Improved means of expression helped students construct better hypotheses on phage host specificity (G = 0.31, p = 0.01) and to explain the plaque assay method (G = 0.33, p = 0.002). At the end of the exercise students also demonstrated improved knowledge and understanding of phage specificity as related to phage therapy in humans (p < 0.001; G = 51).